Research Letter: Concussion Knowledge Is Difficult to Predict From Self-Reported Exposure, Sports Participation, and Education. Issue 5 (23rd September 2022) - Kinmond, Sally; Sullivan, Karen A.; Jaganathan, Kannan Singaravelu
Abstract : Objectives: Increasing concussion knowledge could contribute to improving injury outcomes. Understanding the predictors of concussion knowledge could determine the areas of educational need. This study examined whether individual factors, prior brain injury, prior concussion education, and contact-sports participation predicted concussion knowledge. Design and Setting: Cross-sectional study with recruitment of community volunteers. Participants: An online survey was completed by 525 adults, 443 of whom provided useable responses. Main Measures: The respondents provided background information and completed the Concussion Knowledge Index from the Rosenbaum Concussion Knowledge and Attitudes Survey (RoCKAS). Results: On average, the participants answered 19.8 out of 25 items correctly. A multiple regression model with demographic, injury, and sport-related variables did not significantly predict concussion knowledge. Conclusion: This community sample had higher than expected concussion knowledge (restricted range), but some important misconceptions were still present. The model reflecting a combination of self-reported factors did not predict concussion knowledge. The implications for concussion education are discussed, including the need for targeted education to address specific misconceptions.